Economic policy as expectations management: Keynes' and Friedman's complementary approaches1. Issue 5 (3rd September 2017) - Rivot, Sylvie
Abstract: We investigate how Keynes and Friedman, respectively, address the issue of the disequilibria at stake in a monetary economy through a shared concern for the formation of expectations. We show that Keynes was interested in the coordination of long-term expectations regarding non-monetary assets prospective yields, while Friedman focused on the adaptation of short-term nominal expectations. Regarding the remedies to these disequilibria, both economists called for devices that aim to stabilise market expectations. As a direct outcome, Keynes designed policies that aim to stabilise the long-term state of expectations while Friedman basically aimed at the acceleration of the competitive adjustment process.